2010
DOI: 10.1186/1743-8977-7-41
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles induce CYP1A1 and pro-inflammatory responses via differential pathways in human bronchial epithelial cells

Abstract: BackgroundExposure to diesel engine exhaust particles (DEPs) has been associated with several adverse health outcomes in which inflammation seems to play a key role. DEPs contain a range of different inorganic and organic compounds, including polycyclic aromatic hydrocarbons (PAHs). During the metabolic activation of PAHs, CYP1A1 enzymes are known to play a critical role. In the present study we investigated the potential of a characterised sample of DEPs to induce cytotoxicity, to influence the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 37 publications
14
124
2
1
Order By: Relevance
“…[24] The DEP was collected from the inside of the main exhaust pipe after the diesel engine had been running for 8 weeks, in conjunction with an on-going clinical chamber study. The WSP sample was collected from the interior of a chimney that vented an airtight wood stove burning a mix of hardwoods.…”
Section: Collection and Preparation Of Particle Suspensions And Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] The DEP was collected from the inside of the main exhaust pipe after the diesel engine had been running for 8 weeks, in conjunction with an on-going clinical chamber study. The WSP sample was collected from the interior of a chimney that vented an airtight wood stove burning a mix of hardwoods.…”
Section: Collection and Preparation Of Particle Suspensions And Extractsmentioning
confidence: 99%
“…[24] The percentage of apoptotic and necrotic cells were determined as a fraction of the total number of counted cells.…”
Section: Examination Of Cytotoxicitymentioning
confidence: 99%
“…A similar increase, though of a much higher magnitude, was observed in A549 cells and has also been reported after exposure of DEP or organic extracts of DEP 6,38,40,[43][44][45] . A greater magnitude of increase in the expression of CYP1A1 in IM9 or A549 cells exposed to MC prior to DEP have shown that like in the tissues, PAH metabolising CYPs, enriched following exposure of MC, catalyze the metabolic activation of PAHs present in DEPs in the blood cells.…”
Section: Discussionmentioning
confidence: 62%
“…After inhalation of PM, phagocytic cells including neutrophils and macrophages are recruited to the foreign particle by cytokines and chemokines, and transported by the mucociliary escalator for removal (Donaldson and Tran, 2002). PM induces the release of inflammatory cytokines, such as IL-6, IL-8, GM-CSF, and TNF- (Stone et al, 2007) from immune cells (e.g., macrophages) as well as structural airway cells (Totlandsdal et al, 2010).…”
Section: Innate Immunitymentioning
confidence: 99%